Analisis Pengaruh Tekanan Stakeholder Terhadap Pengungkapan Laporan Keberlanjutan Berdasarkan Gri Indeks - Ken Karunia Megan; Einde Evana; Nurdiono Nurdiono; Neny Desriani (Jurnal Kendali Akuntansi, 2024)
This study aims to determine the impact of stakeholder pressure (environment, employees, consumers, and individual shareholders) on sustainability report disclosure. This quantitative study uses secondary data from annual reports and sustainability reports as sources of information. The study involves companies listed in the Kompas 100 Index from 2020 to 2022 as the population. The sampling technique chosen is purposive sampling, resulting in 41 companies as the sample, with a total of 123 reports observed. The analysis is conducted using multiple linear regression, with IBM SPSS Statistics 25 software as the analytical tool. The findings of the study indicate that pressure from the environment and consumers positively affects sustainability report disclosure. However, pressure from employees and individual shareholders does not have a significant impact on sustainability report disclosure.